Analysis of Concept Understanding Ability in Contextual Teaching And Learning in Quadrilateral Materials Viewed from Students Personality Type - Purwaningsih, Kiky; Zaenuri, Zaenuri; Hidayah, Isti (Department of Mathematics, Universitas Negeri Semarang, 2017)
The purpose of this research was to description mathematical understanding of concept ability in learning CTLbased on personality types. This type of research is qualitative. The subjects of this research consists of 8 students VII H grade in state Junior High School 1 Sumpiuh are two srudents for each personality types Artisan, Idealist, Guardian, and Rational. The techniques to collect data of this research are mathematical understanding of concept test and interviews. Test result and interviews are analyzed based on the mathematical understanding of concept ability indicator by Dirjen Dikdasmen Depdiknas regulation Number 506/C/PP/2004 date 11 November 2004. Data analysis was done with the steps as follows: reduction step, data presentation step, make conclusion step. The result of this research showed that: (1) The result of personality types in a class VII H of 32 students there 4 Artisan students, 15 Idealist student, 3 Guardian student, 9 Rational student, and 1 Artisan and Rational student; (2) Artisant subject tend to be good, competent K1, 2, 3, 5, 6, and 7, but less competent K4. Idealist subject competent K1, 2, 3, 4, 5, 6, and 7. Guardian subject competent K1, 2, 3, and 4, but less competent K5, 6, and 7. Rational subject competent K1, 2, 3, 5, 6, and 7, but less competent K4.